2015
DOI: 10.1523/jneurosci.2370-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Differential Dynamics of Spatial Attention, Position, and Color Coding within the Parietofrontal Network

Abstract: Despite an ever growing knowledge on how parietal and prefrontal neurons encode low-level spatial and color information or higher-level information, such as spatial attention, an understanding of how these cortical regions process neuronal information at the population level is still missing. A simple assumption would be that the function and temporal response profiles of these neuronal populations match that of its constituting individual cells. However, several recent studies suggest that this is not necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 39 publications
4
61
0
Order By: Relevance
“…As compared with our findings of decoding covert attentional shift to subsets of external stimuli, there are other recent studies decoding visuospatial attention directly from the intrinsically driven brain activity patterns evoked by attention6970717273. As our study demonstrates the possibility of seamlessly decoding human top-down processes, if a further refined grid-shaped line array is developed and combined with a more elaborated classification method, a recent study74 provides advances in extending previous studies of decoding visuospatial attention6970717273, which were limited to decoding up to four discrete locations/classes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As compared with our findings of decoding covert attentional shift to subsets of external stimuli, there are other recent studies decoding visuospatial attention directly from the intrinsically driven brain activity patterns evoked by attention6970717273. As our study demonstrates the possibility of seamlessly decoding human top-down processes, if a further refined grid-shaped line array is developed and combined with a more elaborated classification method, a recent study74 provides advances in extending previous studies of decoding visuospatial attention6970717273, which were limited to decoding up to four discrete locations/classes.…”
Section: Discussionsupporting
confidence: 74%
“…As our study demonstrates the possibility of seamlessly decoding human top-down processes, if a further refined grid-shaped line array is developed and combined with a more elaborated classification method, a recent study74 provides advances in extending previous studies of decoding visuospatial attention6970717273, which were limited to decoding up to four discrete locations/classes. The authors found a neuronal signature of direct two-dimensional access to the spatial location of covert attention in macaque prefrontal cortex74.…”
Section: Discussionmentioning
confidence: 77%
“…Although the respective timing of attentional modulations are consistent with LIP driving attentional modulations in MT, these correlations do not provide direct evidence for a causal relationship. An alternative, and perhaps likely possibility is that attentional modulations in visual and parietal cortices are driven by top-down modulation from FEF (Astrand et al, 2015; Gregoriou et al, 2009; Ibos et al, 2013; Moore and Armstrong, 2003; Wardak et al, 2006) and PFC (Bichot et al, 2015; Hussar and Pasternak, 2013; Lennert and Martinez-Trujillo, 2011, 2013; Tremblay et al, 2015). For example, both electrical and pharmacological manipulation of FEF have been shown to produce attention-like modulation of activity in V4 (Armstrong and Moore, 2007; Noudoost and Moore, 2011; Schafer and Moore, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, top-down attention signals are presumed to originate in the FEF (Astrand et al, 2015; Gregoriou et al, 2009; Ibos et al, 2013; Moore and Armstrong, 2003; Wardak et al, 2006) or PFC (Bichot et al, 2015; Hussar and Pasternak, 2013; Lennert and Martinez-Trujillo, 2011, 2013; Tremblay et al, 2015), and are likely to target neurons from several areas simultaneously, including area V4, MT and also LIP (Ekstrom et al, 2008). Therefore, it is unlikely that the effects of attention on LIP activity exclusively result from the integration of the attention-modulated activity of upstream visual neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The fractionation of the timing of arrival of action potential at the target can increase the effective strength of cortico-cortical connections, by favoring temporal summation at the synaptic level. Finally, the long temoral dynamics necessary for encoding complex processes, such as the instructed position of attention, target position and color signals in LIP and FEF (Astrand et al, 2015) can be, at least in part, sustained by the temporally-dispersed input conveyed to these neuronal population by their cortico-cortical connections.…”
Section: Information From Computational Neuroanatomymentioning
confidence: 99%